Pathophysiology of subendocardial ischaemia. - Hoffman, J I (1975)
Most forms of heart disease cause myocardial damage which often is confined to the deep (subendocardial) layer of left ventricular muscle. Much clinical and experimental evidence suggests that subendocardial muscle is prone to ischaemic damage, and a physiological mechanism for this vulnerability is described. Furthermore, experiments suggest that pressures recorded at cardiac catheterization can help to assess if there is subendocardial ischaemia in a variety of lesions in man.